The separation of diastereoisomers by gas-liquid chromatography - Nurok, David (Department of Chemistry, 2015)
The preparation and the gas chromatographic behaviour of several series of diastereoisomeric compounds is described. The series are the following: (1) Alkyl lactates, {2) Afkyl á-alkanoyloxypropionates, (3) Dialkyl esters of 2,3-butanediol, (4) Di-(haloacetic) esters of 2 1 3-butanediol and (5) á,â-Diols. Chromatography was performed at various temperatures and a variety of stationary phases was used. Capillary columns were used for chromatography of series 1 and 2 whereas packed columns were used for series 3 to 5. It was found that for all of the above series nearly all of th compounds could be separated into diastereoisomers. The separability was found to be a function of the chemical structure of the compounds, of the polarity of the stationary phases and of the temperature at which chromatography was performed.